Amendment to national provisions implementing the Hague Convention (Ius Novum, 2020)
The article discusses issues related to the recently amended provisions of the Code of Civil Procedure with regard to proceedings in the case of an application to return a child filed under the Hague Convention. The amended Act changes the jurisdiction of a court in these matters, transferring it from the level of a lowest regional court to selected district courts, and in appeal proceedings, the only competent court is the Court of Appeal in Warsaw. The Act also introduces the possibility of lodging a cassation appeal against the decision of the second-instance court. As the Ministry of Justice, the author of the Bill, directly claims, the aim of the regulation is to ‘protect Polish children’. As a result, the Act raises extralegal emotions. With this in mind, and primarily considering the purpose of the Convention, which is the best interests of the child, the assessment of the amendments should be made with great caution.
Keywords: Hague Convention; civil aspects of international child abduction; child abduction; parental abduction